O livro de didático de ciências da natureza nos centros de educação de jovens e adultos do estado de Goiás - Moreira, Fabíola Correia de Souza Araújo (2017)
A brief historical survey of youth and adult education (EJA) - in Brazil and in Goiás - shows that one modality has historically been on the margins of public educational policies. (PNLDEJA), in 2009, an extremely important and beneficial public policy modality for the use of pedagogical tools. This research analyzes the use of the didactic book of Nature Sciences / Biology, chose the National Program of Didactic Book (PNDL) for a Youth and Adult Education (EJA), high school, in 2014, the attendance of specificities put No Curriculum of the modality in the state network. The purpose of this study was to evaluate the effectiveness of this policy, through the study of documents such as laws and states, a biology curriculum for a mobile modality, the Nature / Biology Sciences book chosen in PNLD-EJA / 2014. Through questionnaires with Teachers and interviews with the representative of the Ministry of Education on the use of LD in the Youth and Adult Education Centers (CEJAS) of the state network, as weaknesses in the implementation of the program. It has been found that the program is still recent, and can be approved with the passing of the editions, an end of which the teachers are co-authors of the process. It is possible to perceive a training plan for the professionals who work in the EJA, aiming at a quality of education in line with a proposal of the network.